Festoons, edema, and malar bags: is there a consensus on aesthetic treatment? - Caroline Silva Costa de Almeida; Kyldery Wendell Moura Cavalcante; Rafael Ximenes Bandeira de Morais; André Luiz Belém Negromonte dos Santos; Eduarda Augusta de Lucena Caldas; Marcel Fernando Miranda Batista Lima; Igor Chaves Gomes Luna; Rafael Anlicoara (Revista Brasileira de Cirurgia Plástica)
Introduction: Periorbital changes are some of the first detectable signs of aging. The most outstanding currently, refers to the rejuvenation of this region, involving the treatment from the eyebrows to the transition orbital-malar, where are festoons, edemas, and malar bags. However, this management is complex, involving several approaches: invasive or noninvasive techniques. Thus, this review aims to describe the scientific evidence of the most current techniques used in the treatment of festoons, edema, and malar bags and to evaluate the complications related to each modality. Methods: The research was carried out in three databases, PubMed, Cochrane, and LILACS - using the descriptors "bolsa malar," "malar mounds," "festoons" and "malar bags" in the period from 2014 to 2019, in English and Portuguese. Results: We selected 13 articles; most of the studies were retrospective reviews (76.9%), seven dealt with noninvasive techniques, three about invasive, and three on the association of techniques. Regarding the procedures described, the noninvasive ones were represented by the use of Kinesio tape, tetracycline injection, doxycycline and hyaluronic acid, and the use of microneedling with radiofrequency. The invasive ones were represented by microaspiration, myocutaneous flap, subperiosteal lift of the middle face, and direct excision. Conclusion: There are numerous techniques for treating festoon and malar bags, but it is up to the plastic surgeon to know its advantages and disadvantages to decide the most appropriate in each situation. Thus, there is no consensus, but it is vital to diagnose correctly to indicate the best treatment.